Indigenous rights to defend land and traditional activities: A case study of the Sami in northern Sweden - Tsiouvalas, Apostolos; Poto, Margherita Paola (2018)
One of the largest remaining unexploited iron ore deposits in Europe is the Kallak Iron Deposit in the province of Norrbotten in northern Sweden, where a significant Sámi population is located. Since 2011, the UK-based company, Beowulf Mining, has begun a large campaign for extraction in northern and southern Kallak. However, the Sámi of the region, together with environmentalists and non-Sámi individuals have drastically expressed their opposition blocking with various ways the processes. The Sámi being aware of the environmental risk have concerns about their ability to drive reindeer across the land, and the impact Beowulf’s operations are likely to have on the reindeer migratory patterns. Nowadays, seven years after the initial application for licensing, theapproval of the application is still pending and Beowulf is pressing more and more the Swedish authorities for a final response in order to start extracting. Only the County Administrative Board of Norrbotten, despite its initial consent, still advocates for Sámi and their reindeer refusing to issue licensing for the British company. Accordingly, this article was designed as a descriptive study of the legal framework of the implementation of this endeavour addressing the legal arguments of both sides as they derive from a qualitative study of official documents, environmental reports, and relative articles of scholars. Concluding, the article illustrates the gaps of legal protection of indigenous land-rights in Sweden presenting their vulnerability to such kind of challenges. Um dos maiores depósitos de minério de ferro ainda não explorados na Europa é o Kallak Iron Deposit, na província de Norrbotten, no norte da Suécia, onde está localizada uma população significativa de Sámi. Desde 2011, a empresa britânica Beowulf Mining iniciou uma grande campanha de extração no norte e no sul de Kallak. No entanto, os Sámi da região, junto com ambientalistas e não-Sámi expressaramdrasticamente seu bloqueio de oposição de várias maneiras pelos processos. Os Sámi ...